On the Importance of Museum Ethnographic Collections for Archaeological Research: the Case of Native Weapons from Tierra del Fuego at the Weltmuseum Wien - Charlin, Judith Emilce (2018)
The use of ethnographic analogies to aid the interpretation of archaeological remains is an important theoretical and methodological tool in archaeological research. Historic records, folklore, ethnographic reports and the most archaeological-driven actualistic research like ethnoarchaeology are the main sources to develop a wide range of analogies, from the function or production techniques of particular objects to activity areas and discard patterns, as well as broader models of socio-political and economical organization (see Binford 1994, 2001; Sillar and Joffré 2016, among others). Native material culture stored in museums provides core material for analogies since only a fraction of the artefacts used in the past are preserved in the archaeological record. Many organic materials, such as baskets, textiles, leathers, woods, among others, do not leave any trace, excepting unusual situations of very good preservation. Prehistoric weapons offer a clear example of these conservation problems. In general the overall technical system, which is mostly composed of perishable materials -such as wooden bows and arrow shafts- is rarely preserved in the archaeological record. The weapon points, mainly the lithic ones, are typically the only remains recovered by archaeologists and according to their morphometric attributes form the base of overall weapon system reconstruction. For this reason, ethnographic weapons from museum collections are a very valuable source of information for the study of technical and functional traits of prehistoric weapons since often preserve the overall technical system. This line of research was the frame of reference in my study of Weltmuseum Wien weapon collections from South America (department in charge of Dr. Claudia Augustat), North America (department in charge of Prof. Dr. Gerard van Bussel) and Oceania and Australia (department in charge of Prof. Dr. Gabriele Weiss). My interests are focused in size and shape variation among weapon systems, especially in their points, according to function and raw material. Here I will present the main results obtained from the morphometric analysis of Tierra del Fuego arrow collections surveyed at Weltmuseum Wien, including also some other Fuegian collections with comparative purposes.